PENGGANTIAN KELAMIN BAGI TRANSEKSUAL DAN AKIBAT HUKUMNYA TERHADAP KEABSAHAN PERKAWINAN DITINJAU DARI UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN - Yeni Astutik; Anjar Sri Ciptorukmi Nugraheni (Jurnal Privat Law, 2020)
AbstractThis article aims to examine the ratification of changes in legal status and gender replacement  procedures in population documents for transsexuals in Indonesia, as well as the legality of marriages for transsexuals in terms of Law Number 1 of 1974 concerning Marriage. The research method used is a type of normative legal research, with a qualitative approach. The legal materials used are primary and  secondary legal materials, with data collection techniques used are literature study or document study  techniques. Based on the results of the study, it was concluded that in Indonesia there are no specific rules regarding sex change, but for judges they cannot refuse a case because the law does not exist or is unclear. Regarding the procedure for changing sexes in population documents regulated in Act Number 23 of 2006 concerning Population Administration and Presidential Regulation of the Republic of Indonesia Number 25 of 2008 concerning Requirements and Procedures for Population Registration and Civil Registration. Then regarding the validity of marriage for transsexuals, from the six  religions  recognized  by  the  government  as  the  official  religion  in  Indonesia,  namely  Islam, Christianity, Catholicism, Hinduism, Buddhism, and Confucianism, do not legalize a marriage carried out by parties, one of whom is a transsexual who has gone through Sex Reassignment Surgery. Keywords: Sex Reassignment; Transsexual; Legality of Marriage.AbstrakArtikel ini bertujuan untuk mengkaji pengesahan perubahan status hukum dan prosedur penggantian  jenis kelamin di dokumen kependudukan bagi transeksual di Indonesia, serta keabsahan perkawinan bagi transeksual ditinjau dari Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan. Metode penelitian yang digunakan adalah jenis penelitian hukum normatif, dengan pendekatan kualitatif. Bahan hukum yang digunakan adalah bahan hukum primer dan sekunder, dengan teknik pengumpulan data yang digunakan adalah teknik studi kepustakaan atau studi dokumen. Berdasarkan hasil penelitian, disimpulkan bahwa di Indonesia belum ada aturan khusus mengenai penggantian jenis kelamin, namun bagi hakim tidak boleh menolak suatu perkara karena Undang-Undang tidak ada atau tidak jelas. Mengenai prosedur penggantian jenis kelamin di dokumen kependudukan diatur dalam  Undang- Undang Nomor 23 Tahun 2006 tentang Administrasi Kependudukan dan Peraturan Presiden Republik Indonesia Nomor 25 Tahun 2008 tentang Persyaratan dan Tata Cara Pendaftaran Penduduk dan Pencatatan Sipil. Kemudian mengenai keabsahan perkawinan bagi transeksual, dari keenam agama yang diakui pemerintah sebagai agama resmi di Indonesia yaitu Islam, Kristen, Katolik, Hindu, Buddha, dan Khonghucu, tidak mensahkan suatu perkawinan yang dilaksanakan oleh para pihak yang salah  satunya seorang transeksual yang telah melalui operasi penggantian kelamin.Kata Kunci: Penggantian Kelamin; Transeksual; Keabsahan Perkawinan.